(untitled) (Islas, 2021)
En medio de la pandemia de la COVID-19 se desarrolla una lucha ideológica sin cuartel, se opone el capital a la vida. Cuba también es objeto de dicho enfrentamiento, pues nuestro proyecto socialista demuestra que no hacen falta riquezas exorbitantes o tecnología de primera generación para velar por la vida de los seres humanos. Hace falta humanismo real. Este trabajo propone un acercamiento al tema desde las opiniones, actuaciones, valoraciones y polémicas desatadas en torno a la pandemia. Amid the pandemic of COVID-19 an ideological fight is being developed without quarter, it opposes capital to life. Cuba is also object of this confrontation, because our socialist project demonstrates that there is no need of an exorbitant wealth or cutting edge technology to save the life of the human beings. Real humanism is what is needed. This paper proposes an approach to this subject from the opinions, actions, evaluations and controversies unleashed around the pandemic.